Causes, Effects and Control of Respiratory Tract Infections Among Reproductive Age Women in Jalingo Local Government Area of Taraba State-Nigeria (Texas Journal of Medical Science, 2023)
This study examined the causes, effects and control of respiratory tract infections among patients in Jalingo Local Government Area of Taraba State. Data were collected from the primary source using survey research design. A sample of 365 respondents was drawn and used to represent the entire population of the study. The research instrument was validated and tested using Alpha cronbach with the reliability coefficient of 0.90. Data collected were analyzed using descriptive statistics of frequency, simple percentage, mean and standard deviation. The study found that, virus with flu, tobacco smoke, respiratory syncytial virus, indoor air burning from burning fuels, dust and chemicals, bacteria as well as fungal infections and staphylococcus aureus were accepted to be the main causes of respiratory tract infections. While congestive heart failure, respiratory failure, death occurs as a result of negligent to proper treatment, abnormal lung functioning, respiratory arrest and blood infection (sepsis) leading to organ shutdown were identified in this study as the major effects of effects of respiratory tract infections among patients in Jalingo Local Government Area of Taraba State. Recommendations: Health professionals and health management should provide adequate vital information to the general public to enlighten them on the preventive measure of respiratory tract infection so as to reduce the menace of the infections to its minimal point as well as promote good health among the populace in the study location and the state as a whole as well as Government and health policy formulators should as a matter of urgency provide substantial and effective measures through programmes and schemes as well as provide adequate vaccines for treatment and management of respiratory tract infections.